Being kind to my socially anxious mind; A study of the relationship between self-compassion and social anxiety - Schwanen, Guna (Student Undergraduate Research E-journal!, 2015)
Self-compassion stands for a kind, accepting, and therefore more adaptive attitude towards oneself. In the face of social failure, self-compassion might be particularly useful for people with social anxiety. The present study aimed to examine the relationship between self-compassion and social anxiety. A sample of 120 individuals completed online questionnaires. Results showed that social anxiety, fear of negative evaluation, and self-focused attention were strongly related to self-compassion. Thus, self-compassion might be a useful construct for people with social anxiety and explicit training in self-compassion may give rise to a more caring and kinder attitude towards oneself during social failure.